TINJAUAN UU. PERKAWINAN NOMOR 1 TAHUN 1974 TENTANG PERNIKAHAN SIRRI DALAM ACARA KHTBAH - Muhammad Burhanuddin; Abd. Basit Misbachul Fitri (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
This reaserch takes the title Marriage at a Sermon event in the review of Law number 16 of 2019 (Case study in Pakel Village, Bareng District, Jombang Regency). There are two questions. First, what is the background for carrying out a sirri wedding at the Khitbah event? Second, how is the review of Law number 1 of 1974 Sirri marriage at the Khitbah event. The research we collected through interviews and documents was then analyzed using narrative techniques and content, using an analytical deductive mindset, namely the data was analyzed by reviewing Law number 1 of 1974 on Siri Marriage at the Khitbah event. The research we collected through interviews and documents was then analyzed using narrative techniques and content, using an analytical deductive mindset, namely the data was analyzed by reviewing Law number 1 of 1974 on Siri Marriage at the Khitbah event.